Co-seismic and post-seismic behavior of an existed shallow foundation and super structure system on a natural sand/silt layered ground. Issue 1 (7th March 2016) - Bao, Xiaohua; Ye, Guanlin; Ye, Bin; Fu, Yanbin; Su, Dong
Abstract : Purpose: – The purpose of this paper is to evaluate the co-seismic and post-seismic behaviors of an existed soil-foundation system in an actual alternately layered sand/silt ground including pore water pressure, acceleration response, and displacement et al. during and after earthquake. Design/methodology/approach: – The evaluation is performed by finite element method and the simulation is performed using an effective stress-based 2D/3D soil-water coupling program DBLEAVES. The calculation is carried out through static-dynamic-static three steps. The soil behavior is described by a new rotational kinematic hardening elasto-plastic cyclic mobility constitutive model, while the footing and foundation are modeled as elastic rigid elements. Findings: – The shallow (short-pile type) foundation has a better capacity of resisting ground liquefaction but large differential settlement occurred. Moreover, most part of the differential settlement occurred during earthquake motion. Attention should be paid not only to the liquefaction behavior of the ground during the earthquake motion, but also the long-term settlement after earthquake should be given serious consideration. Originality/value: – The co-seismic and post-seismic behavior of a complex ground which contains sand and silt layers, especially long-term settlement over a period of several weeks or even years after the earthquake, has been clarified sufficiently. In some critical condition, even if the seismic resistance is satisfied with the design code for building, detailed calculation may reveal the risk of under estimation of differential settlement that may give rise to serious problems.